Ethical implications of AI in healthcare - An introductory piece - Robin Mekvan, Andy Miah (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The ethical implications of integrating Artificial Intelligence (AI) into healthcare have raised significant concerns. With the advancement of AI technology and its increasing integration into medical procedures, there is a pressing worry about the potential for AI systems to perpetuate existing biases and inequalities. This concern is rooted in the possibility of unfair treatment of specific patient demographics, which could worsen existing health disparities. In this interview, Robin Mekvan spoke with Professor Andy Miah, the Chair of Science Communication and Future Media at the University of Salford. Professor Miah also directs the SciComm Space and leads the Metaverse Special Interest Group, along with overseeing the ENGAGEMENT FORUM that focuses on Community and Public Engagement. As the university's AI Ethics lead, he actively promotes responsible AI integration while advising global organisations on the ethical considerations of emerging technologies.
Keywords: artificial intelligence; data efficiency; public healthcare; data security; AI accountability; patient involvement; regulatory frameworks; patient privacy; preventative medicine; ethical implications